meta analisis Pengaruh Metode Hypnoteaching terhadap beberapa hasil pembelajaran - Indra Darmawan; Burhanudin Tolla; Yetti Supriyati (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2021)
The purpose of this study was to re-analyze the effect of the Hypnoteaching learning method on several learning outcomes. The method used in this research is meta-analysis. The research begins by tracing the relevant research results for analysis. Data was collected by searching electronic journals through Google Scholar and Google Scholar with the keywords